The production of dehydrated carrots, corn, garlic and onions - Hidalgo, Christian Jeffrey; Mateo, William Gilbert; Salazar, Marilen; Villanueva, Ma. Victoria (Diliman, Quezon City College of Engineering, 1999)
Products: Dehydrated carrots, corn, garlic flakes, garlic powder, onion flakes, onion powder -- Plant location: San Gabriel, Sta. Maria, Bulacan -- Annual production: Dehydrated carrots - 15630 kg, dehydrated corn - 25396.2 kg, Dehydrated garlic flakes - 23652.72 kg, Dehydrated garlic powder - 55189.68 kg, Dehydrated onion flakes - 13681.44 kg, Dehydrated onion powder - 31923.36 kg -- Annual gross sales: Php 30,472,368.16 -- Annual income: Php 5,299,356.98 -- Total investment cost: Php 28,186,005.33 -- Product unit cost: Dehydrated carrots - Php 171.06/kg, dehydrated corn - Php 63.89/kg, Dehydrated garlic flakes - Php 139.28/kg, Dehydrated garlic powder - Php 139.28/kg, Dehydrated onion flakes - Php 75.49/kg, Dehydrated onion powder - Php 75.49/kg -- Product selling price: Dehydrated carrots - Php 230/kg, dehydrated corn - Php 429/kg, Dehydrated garlic flakes - Php 178/kg, Dehydrated garlic powder - Php 175/kg, Dehydrated onion flakes - Php 122/kg, Dehydrated onion powder - Php 120/kg -- Return on investment: 18.8% -- Payback period: 1.32 years (1 year and three months)
Submitted in partial fulfillment of the requirements in ChE 142 Chemical Engineering Plant Design
Keywords: Factories -- Design and construction; Agricultural processing plants; Dried vegetables